Leksikalizacija prostorskih razmerij v slovenščini - Jakop, Nataša (Slavistična revija, 2014)
With a linguistic pragmatics analysis of the chosen linguistic means the author first identifies linguistic components with spatial reference where the expression of spatiality is based on dynamic, relative understanding of space, which depends on the observer and often on the temporal dimension. After that, she explains their lexicalization.
Keywords: izkustveni realizem; prislov; prostorski prislovi; Slovene; slovenščina